Profitabilitas UMKM: Analisis Perencanaan Laba Dengan Pendekatan Margin Of Safety - Al Iqdam Bima Habbatil Izzi; Gideon Setyo Budiwitjaksono (Akuntansi, 2023)
The purpose of this study was to analyze profit planning with a margin of safety approach in the Pia business at UD Berkah Abadi in 2019-2022. This research uses descriptive quantitative type, with data collection through financial reports for 2019-2022 Data analysis uses the Miles Huberman model with the stages of condensation, display and data verification. The research findings show that with a large margin of safety, it will provide financial security so as not to experience losses and to achieve profits by conducting product disevsity, product innovation, conducting cost analysis and proper cost mapping. This research has implications for profit planning based on the calculation of margin of safety for Small and Medium Enterprises. This research also supports further research to analyze profit planning through other methods. So that it can be used to see opportunities and market share for pia products to increase sales and profits.